Catalytic effect of (Ti0.85Zr0.15)1.05Mn1.2Cr0.6V0.1Cu0.1 on hydrogen storage properties of ultrafine magnesium particles. Issue 55 (10th July 2017) - Liu, Peng; Ma, Xiujuan; Xie, Xiubo; Li, Xingguo; Liu, Tong
Abstract : The Mg–(Ti0.85 Zr0.15 )1.05 Mn1.2 Cr0.6 V0.1 Cu0.1 composites synthesized by milling TiMn2 alloy with ultrafine Mg particles display significantly enhanced hydrogen storage properties. Abstract : In order to improve hydrogen storage properties of magnesium, (Ti0.85 Zr0.15 )1.05 Mn1.2 Cr0.6 V0.1 Cu0.1 (TiMn2 type) alloy particles have been added into magnesium ultrafine particles produced by a hydrogen plasma-metal reaction approach by ball milling. The (Ti0.85 Zr0.15 )1.05 Mn1.2 Cr0.6 V0.1 Cu0.1 particles are uniformly dispersed on the surface of magnesium. The addition of (Ti0.85 Zr0.15 )1.05 Mn1.2 Cr0.6 V0.1 Cu0.1 alloy improves both the hydrogen storage capacity and kinetics of magnesium. The magnesium–5 wt% (Ti0.85 Zr0.15 )1.05 Mn1.2 Cr0.6 V0.1 Cu0.1 composite can absorb 6.00 wt% H2 within 60 minutes at 523 K and desorb 6.00 wt% H2 within 15 minutes at 623 K. With the increase of (Ti0.85 Zr0.15 )1.05 Mn1.2 Cr0.6 V0.1 Cu0.1, the hydrogenation and dehydrogenation kinetics of the composites improve. The apparent activation energies of magnesium– x wt% (Ti0.85 Zr0.15 )1.05 Mn1.2 Cr0.6 V0.1 Cu0.1 ( x = 5, 10, 30) composites for hydrogen absorption and desorption are 67.52, 65.80, 60.99 kJ mol −1 and 121.37, 116.68, 77.25 kJ mol −1, respectively. The enhanced hydrogen storage capacities and kinetics can be attributed to the effective catalysis of the (Ti0.85 Zr0.15 )1.05 Mn1.2 Cr0.6 V0.1 Cu0.1 alloy and ultrafine size of magnesium particles.